A sewage treatment agent and preparation method thereof
The sewage treatment agent prepared by modifying components such as enhanced efficiency powder solves the problems of high concentration, low transparency and obvious odor in the prior art, and effectively absorb and precipitate impurities, improve the transparency of water and remove odor.
Patent Information
- Application Number
- CN202310414103.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-04-18
AI Technical Summary
The existing heavy metal wastewater treatment agents have high concentrations of suspensions, low transparency, and obvious odor, making it difficult to completely remove impurities and odors.
Sewage treatment agents are prepared by modified synergistic powder, calcium aluminate, modified activated carbon, flocculant, calcium sulfate, modified iron tetraoxide nanoparticles, acrylamide graft copolymer and silicate. The adsorption and precipitation effect of the material is improved through the modification treatment.
Effectively adsorb impurities in sewage, reduce the content of suspended matter, improve transparency, avoid dark water polluting the river, and there is no obvious odor in the treated sewage.
Smart Images

Figure CN116177822B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medicaments, and in particular to a sewage treatment medicament and a preparation method thereof. Background Art
[0002] The patent with application number CN201911273176.3 discloses a heavy metal sewage treatment agent. The above-mentioned heavy metal treatment agent, the mixed dissolution process of the heavy metal treatment agent forms a porous powder carrier of montmorillonite, sodium alginate and calcium chloride, which is coated with a variety of active groups under the coagulation of polyacrylamide and chitosan, and can undergo physical and chemical reactions such as complexation, chelation, adsorption, and exchange with heavy metals. It can efficiently granulate heavy metals in different forms in the aqueous solution, thereby reducing the dosage of heavy metal treatment agents; it can quickly generate easily removable colloidal insolubles in a very short time of 1-5 minutes, thereby achieving the effect of removing heavy metals from sewage.
[0003] However, this heavy metal sewage treatment agent also has some problems. For example, the concentration of suspended solids after sewage treatment is still high, and there are still a large number of impurities suspended in the water, which are difficult to remove. Moreover, the color is still relatively dark and the transparency is low. After being discharged into the river, it is easy to cause the river to change color. At the same time, the treated sewage has an obvious odor, and special odor removal is required later. Summary of the invention
[0004] Based on the problems of high suspended matter concentration, low transparency and obvious odor in the background technology, the present invention proposes a sewage treatment agent and a preparation method thereof.
[0005] The invention provides a sewage treatment agent, which comprises 40 to 50 parts of modified synergistic powder, 15 to 20 parts of calcium aluminate, 10 to 15 parts of modified activated carbon, 5 to 10 parts of flocculant, 5 to 10 parts of calcium sulfate, 1 to 5 parts of modified ferrosoferric oxide nanoparticles, 1 to 5 parts of acrylamide graft copolymer and 1 to 2 parts of silicate. The modified synergistic powder comprises montmorillonite, kaolinite, fly ash, zeolite and lime powder, and is modified at high temperature. The modified activated carbon uses polyimide, hydrochloric acid solution, silane coupling agent and alcohol. The modified flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate. The modified ferrosoferric oxide nanoparticles are modified using a silane coupling agent, phosphoethanolamine and sodium acrylate. The sewage treatment agent is prepared by modified synergistic powder, calcium aluminate, modified activated carbon, flocculant, calcium sulfate, modified ferrosoferric oxide nanoparticles, acrylamide graft copolymer and silicate. The sewage treatment agent can effectively adsorb impurities in the sewage and drive the impurities to precipitate, reduce the content of suspended matter, improve transparency, avoid dark water polluting the river, and the treated sewage has no obvious odor.
[0006] Preferably, the ratio of montmorillonite, kaolinite, fly ash, zeolite and lime powder in the modified synergistic powder is controlled at 3:1:2:1:3, and the montmorillonite, kaolinite and zeolite are all ground until they pass through a 100-mesh sieve to ensure the dispersibility of the materials, so that the materials can be better integrated and the compatibility is improved.
[0007] Preferably, the preparation method of the modified synergistic powder is as follows: montmorillonite, kaolinite, fly ash, zeolite and lime powder are poured into a stirring device for stirring and mixing, the stirring temperature is controlled at 35°C to 45°C, the stirring speed is controlled at 240r / min to 320r / min, deionized water is added after stirring for 5 minutes and stirring is continued, a mixed material is obtained after stirring for 5 minutes to 15 minutes, the mixed material is dried in a drying oven, a block material is obtained after drying, the block material is broken into particles passing through a 10-mesh sieve, the particles are poured into a roasting device for roasting, the roasting temperature is controlled at 600°C to 640°C, the roasting is performed for 60 minutes to 110 minutes, the material is poured out and ground until the material passes through a 200-mesh sieve to obtain a modified synergistic powder, and the prepared modified synergistic powder can be used as a main material, thereby improving the effect of the agent.
[0008] Preferably, the preparation method of the modified activated carbon is as follows: obtaining activated carbon, pouring the activated carbon into a hydrochloric acid solution and soaking it, the mass concentration of the hydrochloric acid solution is 45% to 65%, the soaking temperature is controlled at 65°C to 75°C, washing it with deionized water after 15 minutes, pouring it into polyimide, silane coupling agent and alcohol after drying, starting an ultrasonic generator for treatment, controlling the power of the ultrasonic wave at 1200W to 1500W, and the frequency of the ultrasonic wave at 22KHz to 28KHz, after 60 minutes to 100 minutes of ultrasonic reaction, washing the activated carbon again with deionized water, and obtaining modified activated carbon after drying, wherein the modified activated carbon can adsorb more impurities, and it can be soaked in water for a long time, and the effect lasts for a long time.
[0009] Preferably, the flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate in a ratio of 6:2:2, and the potassium aluminum sulfate dodecahydrate is a powdered material. The flocculant can be used to allow impurities to gather close to each other and then sink under the action of gravity.
[0010] Preferably, the preparation method of the flocculant is as follows: potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate are poured into deionized water, the stirring temperature is controlled at 55°C to 65°C, the stirring speed is controlled at 320r / min to 400r / min, and after stirring for 15 to 30 minutes, the mixture is dehydrated and dried, and poured into a grinder for grinding to obtain a flocculant. The prepared flocculant has good flocculation effect and can significantly reduce the content of suspended matter.
[0011] Preferably, the ratio of ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate in the modified ferroferric oxide nanoparticles is controlled at 3:0.5:2.5:4, and the ferroferric oxide nanoparticles are nano-scale ferroferric oxide powder. The modified ferroferric oxide nanoparticles can adsorb more heavy metals.
[0012] Preferably, the preparation method of the modified ferroferric oxide nanoparticles is as follows: ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate are uniformly mixed and poured into a grinding device for grinding, and then poured into a plasma treatment reaction device after uniform grinding, wherein the vacuum degree inside the plasma treatment reaction device is 4Pa to 4.2Pa, a radio frequency power supply is used for discharge treatment, and then the mixture is cleaned and dried to obtain modified ferroferric oxide nanoparticles. The modified ferroferric oxide nanoparticles have a good effect of adsorbing heavy metals and can reduce the content of heavy metals in water.
[0013] Preferably, the materials of the sewage treatment agent are 47 parts of modified synergistic powder, 18 parts of calcium aluminate, 13 parts of modified activated carbon, 7 parts of flocculant, 6 parts of calcium sulfate, 4 parts of modified ferrosoferric oxide nanoparticles, 3 parts of acrylamide graft copolymer and 2 parts of silicate, which can achieve the best effect.
[0014] A method for preparing a sewage treatment agent comprises the following steps:
[0015] S1: obtain modified synergistic powder, pour it into deionized water for mixing, add calcium aluminate after mixing evenly, control the stirring temperature at 45°C to 65°C, control the stirring speed at 240r / min to 320r / min, and stir for 15 minutes to 30 minutes to obtain a mixed solution;
[0016] S2: Pour the modified activated carbon and calcium sulfate into the mixed solution, increase the stirring speed to 320r / min-400r / min, and stir for 5-15 minutes to obtain a mixed solution;
[0017] S3: pouring the acrylamide graft copolymer and the silicate into the blended liquid, raising the stirring temperature to 65° C. to 95° C., reducing the stirring speed to 240 r / min to 320 r / min, stirring for 45 to 60 minutes and then drying to obtain a blend;
[0018] S4: Add the flocculant and modified ferroferric oxide nanoparticles into the blend, pour into a grinding device, grind evenly, and obtain a sewage treatment agent.
[0019] Beneficial effects of the present invention:
[0020] The sewage treatment agent is prepared by modified synergistic powder, calcium aluminate, modified activated carbon, flocculant, calcium sulfate, modified ferroferric oxide nanoparticles, acrylamide graft copolymer and silicate. The sewage treatment agent can effectively adsorb impurities in the sewage, drive the impurities to precipitate, reduce the suspended matter content, improve transparency, avoid dark water polluting the river, and the treated sewage has no obvious odor. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The working flow chart proposed by the present invention. DETAILED DESCRIPTION
[0022] The present invention will be further explained below in conjunction with specific embodiments.
[0023] Reference Figure 1 , Embodiment 1
[0024] In this embodiment, a sewage treatment agent is proposed, which includes 46 parts of modified synergistic powder, 16 parts of calcium aluminate, 14 parts of modified activated carbon, 7 parts of flocculant, 7 parts of calcium sulfate, 3 parts of modified ferroferric oxide nanoparticles, 5 parts of acrylamide graft copolymer and 2 parts of silicate, the modified synergistic powder includes montmorillonite, kaolinite, fly ash, zeolite and lime powder, which are modified by high temperature, the modified activated carbon is modified by polyimide, hydrochloric acid solution, silane coupling agent and alcohol, the flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate, the modified ferroferric oxide nanoparticles are modified by silane coupling agent, phosphoethanolamine and sodium acrylate, and the montmorillonite, kaolinite, fly ash, zeolite and lime in the modified synergistic powder are modified by 1% mol / l 2% mol / l 2% mol / l The powder ratio is controlled at 3:1:2:1:3, montmorillonite, kaolinite and zeolite are all ground until they pass a 100-mesh sieve. The preparation method of the modified synergistic powder is as follows: montmorillonite, kaolinite, fly ash, zeolite and lime powder are poured into a stirring device for stirring and mixing, the stirring temperature is controlled at 40°C, the stirring speed is controlled at 290r / min, deionized water is added after stirring for 5 minutes, and stirring is continued for 7 minutes to obtain a mixed material, and the mixed material is dried in a drying box to obtain a block material after drying, the block material is broken into particles passing a 10-mesh sieve, the particles are poured into a roasting device for roasting, the roasting temperature is controlled at 620°C, the roasting is carried out for 80 minutes, and the material is poured out and ground until the material passes a 200-mesh sieve to obtain To the modified synergistic powder, the preparation method of modified activated carbon: obtain activated carbon, pour the activated carbon into a hydrochloric acid solution and soak it, the mass concentration of the hydrochloric acid solution is 55%, the soaking temperature is controlled at 69°C, and after 15 minutes, it is washed with deionized water, and after drying, it is poured into polyimide, silane coupling agent and alcohol, and an ultrasonic generator is started for treatment. The power of the ultrasonic wave is controlled at 1500W, and the frequency of the ultrasonic wave is controlled at 28KHz. After 60 minutes of ultrasonic reaction, the activated carbon is washed again with deionized water, and the modified activated carbon is obtained after drying. The flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate in a ratio of 6:2:2. Potassium aluminum sulfate dodecahydrate is selected as a powder material. The preparation method of the flocculant: potassium aluminum sulfate dodecahydrate, iron salt and Aluminum sulfate is poured into deionized water, the stirring temperature is controlled at 58°C, the stirring speed is controlled at 390r / min, and after stirring for 17 minutes, it is dehydrated and dried, and poured into a grinder for grinding to obtain a flocculant. The ratio of ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate in the modified ferroferric oxide nanoparticles is controlled at 3:0.5:2.5:4. The ferroferric oxide nanoparticles are nano-scale ferroferric oxide powder. The preparation method of the modified ferroferric oxide nanoparticles is as follows: the ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate are mixed evenly, poured into a grinding device for grinding, and poured into a plasma treatment reaction device after grinding evenly. The vacuum degree inside the plasma treatment reaction device is 4.2Pa, using radio frequency power for discharge treatment, and then washing and drying to obtain modified ferroferric oxide nanoparticles.
[0025] A method for preparing a sewage treatment agent comprises the following steps:
[0026] S1: obtain modified synergistic powder, pour it into deionized water for mixing, add calcium aluminate after mixing evenly, control the stirring temperature at 61°C, control the stirring speed at 270r / min, and stir for 24 minutes to obtain a mixed solution;
[0027] S2: Pour the modified activated carbon and calcium sulfate into the mixed solution, increase the stirring speed to 360r / min, and stir for 11 minutes to obtain a mixed solution;
[0028] S3: pouring the acrylamide graft copolymer and the silicate into the blended liquid, raising the stirring temperature to 86° C., reducing the stirring speed to 260 r / min, stirring for 55 minutes and then drying to obtain a blend;
[0029] S4: Add the flocculant and modified ferroferric oxide nanoparticles into the blend, pour into a grinding device, grind evenly, and obtain a sewage treatment agent.
[0030] Reference Figure 1 , Embodiment 2
[0031] In this embodiment, a sewage treatment agent is proposed, which includes 47 parts of modified synergistic powder, 18 parts of calcium aluminate, 13 parts of modified activated carbon, 7 parts of flocculant, 6 parts of calcium sulfate, 4 parts of modified ferroferric oxide nanoparticles, 3 parts of acrylamide graft copolymer and 2 parts of silicate, the modified synergistic powder includes montmorillonite, kaolinite, fly ash, zeolite and lime powder, which are modified by high temperature, the modified activated carbon is modified by polyimide, hydrochloric acid solution, silane coupling agent and alcohol, the flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate, the modified ferroferric oxide nanoparticles are modified by silane coupling agent, phosphoethanolamine and sodium acrylate, and the montmorillonite, kaolinite, fly ash, zeolite and lime in the modified synergistic powder are modified by 1% mol / l 2O3 and 1% mol / l 2O3. The powder ratio is controlled at 3:1:2:1:3, montmorillonite, kaolinite and zeolite are all ground until they pass a 100-mesh sieve. The preparation method of the modified synergistic powder is as follows: montmorillonite, kaolinite, fly ash, zeolite and lime powder are poured into a stirring device for stirring and mixing, the stirring temperature is controlled at 40°C, the stirring speed is controlled at 290r / min, deionized water is added after stirring for 5 minutes, and stirring is continued for 7 minutes to obtain a mixed material, and the mixed material is dried in a drying box to obtain a block material after drying, the block material is broken into particles passing a 10-mesh sieve, the particles are poured into a roasting device for roasting, the roasting temperature is controlled at 620°C, the roasting is carried out for 80 minutes, and the material is poured out and ground until the material passes a 200-mesh sieve to obtain To the modified synergistic powder, the preparation method of modified activated carbon: obtain activated carbon, pour the activated carbon into a hydrochloric acid solution and soak it, the mass concentration of the hydrochloric acid solution is 55%, the soaking temperature is controlled at 69°C, and after 15 minutes, it is washed with deionized water, and after drying, it is poured into polyimide, silane coupling agent and alcohol, and an ultrasonic generator is started for treatment. The power of the ultrasonic wave is controlled at 1500W, and the frequency of the ultrasonic wave is controlled at 28KHz. After 60 minutes of ultrasonic reaction, the activated carbon is washed again with deionized water, and the modified activated carbon is obtained after drying. The flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate in a ratio of 6:2:2. Potassium aluminum sulfate dodecahydrate is selected as a powder material. The preparation method of the flocculant: potassium aluminum sulfate dodecahydrate, iron salt and Aluminum sulfate is poured into deionized water, the stirring temperature is controlled at 58°C, the stirring speed is controlled at 390r / min, and after stirring for 17 minutes, it is dehydrated and dried, and poured into a grinder for grinding to obtain a flocculant. The ratio of ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate in the modified ferroferric oxide nanoparticles is controlled at 3:0.5:2.5:4. The ferroferric oxide nanoparticles are nano-scale ferroferric oxide powder. The preparation method of the modified ferroferric oxide nanoparticles is as follows: the ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate are mixed evenly, poured into a grinding device for grinding, and poured into a plasma treatment reaction device after grinding evenly. The vacuum degree inside the plasma treatment reaction device is 4.2Pa, using radio frequency power for discharge treatment, and then washing and drying to obtain modified ferroferric oxide nanoparticles.
[0032] A method for preparing a sewage treatment agent comprises the following steps:
[0033] S1: obtain modified synergistic powder, pour it into deionized water for mixing, add calcium aluminate after mixing evenly, control the stirring temperature at 61°C, control the stirring speed at 270r / min, and stir for 24 minutes to obtain a mixed solution;
[0034] S2: Pour the modified activated carbon and calcium sulfate into the mixed solution, increase the stirring speed to 360r / min, and stir for 11 minutes to obtain a mixed solution;
[0035] S3: pouring the acrylamide graft copolymer and the silicate into the blended liquid, raising the stirring temperature to 86° C., reducing the stirring speed to 260 r / min, stirring for 55 minutes and then drying to obtain a blend;
[0036] S4: Add the flocculant and modified ferroferric oxide nanoparticles into the blend, pour into a grinding device, grind evenly, and obtain a sewage treatment agent.
[0037] Reference Figure 1 , Embodiment 3
[0038] In this embodiment, a sewage treatment agent is proposed, which includes 49 parts of modified synergistic powder, 16 parts of calcium aluminate, 11 parts of modified activated carbon, 9 parts of flocculant, 7 parts of calcium sulfate, 4 parts of modified ferroferric oxide nanoparticles, 2 parts of acrylamide graft copolymer and 2 parts of silicate, the modified synergistic powder includes montmorillonite, kaolinite, fly ash, zeolite and lime powder, which are modified by high temperature, the modified activated carbon is modified by polyimide, hydrochloric acid solution, silane coupling agent and alcohol, the flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate, the modified ferroferric oxide nanoparticles are modified by silane coupling agent, phosphoethanolamine and sodium acrylate, and the montmorillonite, kaolinite, fly ash, zeolite and lime in the modified synergistic powder are modified by 1% mol / l 2O3 and 1% mol / l 2O3. The powder ratio is controlled at 3:1:2:1:3, montmorillonite, kaolinite and zeolite are all ground until they pass a 100-mesh sieve. The preparation method of the modified synergistic powder is as follows: montmorillonite, kaolinite, fly ash, zeolite and lime powder are poured into a stirring device for stirring and mixing, the stirring temperature is controlled at 40°C, the stirring speed is controlled at 290r / min, deionized water is added after stirring for 5 minutes, and stirring is continued for 7 minutes to obtain a mixed material, and the mixed material is dried in a drying box to obtain a block material after drying, the block material is broken into particles passing a 10-mesh sieve, the particles are poured into a roasting device for roasting, the roasting temperature is controlled at 620°C, the roasting is carried out for 80 minutes, and the material is poured out and ground until the material passes a 200-mesh sieve to obtain To the modified synergistic powder, the preparation method of modified activated carbon: obtain activated carbon, pour the activated carbon into a hydrochloric acid solution and soak it, the mass concentration of the hydrochloric acid solution is 55%, the soaking temperature is controlled at 69°C, and after 15 minutes, it is washed with deionized water, and after drying, it is poured into polyimide, silane coupling agent and alcohol, and an ultrasonic generator is started for treatment. The power of the ultrasonic wave is controlled at 1500W, and the frequency of the ultrasonic wave is controlled at 28KHz. After 60 minutes of ultrasonic reaction, the activated carbon is washed again with deionized water, and the modified activated carbon is obtained after drying. The flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate in a ratio of 6:2:2. Potassium aluminum sulfate dodecahydrate is selected as a powder material. The preparation method of the flocculant: potassium aluminum sulfate dodecahydrate, iron salt and Aluminum sulfate is poured into deionized water, the stirring temperature is controlled at 58°C, the stirring speed is controlled at 390r / min, and after stirring for 17 minutes, it is dehydrated and dried, and poured into a grinder for grinding to obtain a flocculant. The ratio of ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate in the modified ferroferric oxide nanoparticles is controlled at 3:0.5:2.5:4. The ferroferric oxide nanoparticles are nano-scale ferroferric oxide powder. The preparation method of the modified ferroferric oxide nanoparticles is as follows: the ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate are mixed evenly, poured into a grinding device for grinding, and poured into a plasma treatment reaction device after grinding evenly. The vacuum degree inside the plasma treatment reaction device is 4.2Pa, using radio frequency power for discharge treatment, and then washing and drying to obtain modified ferroferric oxide nanoparticles.
[0039] A method for preparing a sewage treatment agent comprises the following steps:
[0040] S1: obtain modified synergistic powder, pour it into deionized water for mixing, add calcium aluminate after mixing evenly, control the stirring temperature at 61°C, control the stirring speed at 270r / min, and stir for 24 minutes to obtain a mixed solution;
[0041] S2: Pour the modified activated carbon and calcium sulfate into the mixed solution, increase the stirring speed to 360r / min, and stir for 11 minutes to obtain a mixed solution;
[0042] S3: pouring the acrylamide graft copolymer and the silicate into the blended liquid, raising the stirring temperature to 86° C., reducing the stirring speed to 260 r / min, stirring for 55 minutes and then drying to obtain a blend;
[0043] S4: Add the flocculant and modified ferroferric oxide nanoparticles into the blend, pour into a grinding device, grind evenly, and obtain a sewage treatment agent.
[0044] Reference Figure 1 , Embodiment 4
[0045] In this embodiment, a sewage treatment agent is proposed, which includes 50 parts of modified synergistic powder, 17 parts of calcium aluminate, 13 parts of modified activated carbon, 5 parts of flocculant, 8 parts of calcium sulfate, 2 parts of modified ferroferric oxide nanoparticles, 4 parts of acrylamide graft copolymer and 1 part of silicate, the modified synergistic powder includes montmorillonite, kaolinite, fly ash, zeolite and lime powder, which are modified by high temperature, the modified activated carbon is modified by polyimide, hydrochloric acid solution, silane coupling agent and alcohol, the flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate, the modified ferroferric oxide nanoparticles are modified by silane coupling agent, phosphoethanolamine and sodium acrylate, and the montmorillonite, kaolinite, fly ash, zeolite and lime in the modified synergistic powder are modified by 1 part of silicate. The powder ratio is controlled at 3:1:2:1:3, montmorillonite, kaolinite and zeolite are all ground until they pass a 100-mesh sieve. The preparation method of the modified synergistic powder is as follows: montmorillonite, kaolinite, fly ash, zeolite and lime powder are poured into a stirring device for stirring and mixing, the stirring temperature is controlled at 40°C, the stirring speed is controlled at 290r / min, deionized water is added after stirring for 5 minutes, and stirring is continued for 7 minutes to obtain a mixed material, and the mixed material is dried in a drying box to obtain a block material after drying, the block material is broken into particles passing a 10-mesh sieve, the particles are poured into a roasting device for roasting, the roasting temperature is controlled at 620°C, the roasting is carried out for 80 minutes, and the material is poured out and ground until the material passes a 200-mesh sieve to obtain To the modified synergistic powder, the preparation method of modified activated carbon: obtain activated carbon, pour the activated carbon into a hydrochloric acid solution and soak it, the mass concentration of the hydrochloric acid solution is 55%, the soaking temperature is controlled at 69°C, and after 15 minutes, it is washed with deionized water, and after drying, it is poured into polyimide, silane coupling agent and alcohol, and an ultrasonic generator is started for treatment. The power of the ultrasonic wave is controlled at 1500W, and the frequency of the ultrasonic wave is controlled at 28KHz. After 60 minutes of ultrasonic reaction, the activated carbon is washed again with deionized water, and the modified activated carbon is obtained after drying. The flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate in a ratio of 6:2:2. Potassium aluminum sulfate dodecahydrate is selected as a powder material. The preparation method of the flocculant: potassium aluminum sulfate dodecahydrate, iron salt and Aluminum sulfate is poured into deionized water, the stirring temperature is controlled at 58°C, the stirring speed is controlled at 390r / min, and after stirring for 17 minutes, it is dehydrated and dried, and poured into a grinder for grinding to obtain a flocculant. The ratio of ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate in the modified ferroferric oxide nanoparticles is controlled at 3:0.5:2.5:4. The ferroferric oxide nanoparticles are nano-scale ferroferric oxide powder. The preparation method of the modified ferroferric oxide nanoparticles is as follows: the ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate are mixed evenly, poured into a grinding device for grinding, and poured into a plasma treatment reaction device after grinding evenly. The vacuum degree inside the plasma treatment reaction device is 4.2Pa, using radio frequency power for discharge treatment, and then washing and drying to obtain modified ferroferric oxide nanoparticles.
[0046] A method for preparing a sewage treatment agent comprises the following steps:
[0047] S1: obtain modified synergistic powder, pour it into deionized water for mixing, add calcium aluminate after mixing evenly, control the stirring temperature at 61°C, control the stirring speed at 270r / min, and stir for 24 minutes to obtain a mixed solution;
[0048] S2: Pour the modified activated carbon and calcium sulfate into the mixed solution, increase the stirring speed to 360r / min, and stir for 11 minutes to obtain a mixed solution;
[0049] S3: pouring the acrylamide graft copolymer and the silicate into the blended liquid, raising the stirring temperature to 86° C., reducing the stirring speed to 260 r / min, stirring for 55 minutes and then drying to obtain a blend;
[0050] S4: Add the flocculant and modified ferroferric oxide nanoparticles into the blend, pour into a grinding device, grind evenly, and obtain a sewage treatment agent.
[0051] Reference Figure 1 Embodiment 5
[0052] In this embodiment, a sewage treatment agent is proposed, which includes 45 parts of modified synergistic powder, 16 parts of calcium aluminate, 14 parts of modified activated carbon, 8 parts of flocculant, 7 parts of calcium sulfate, 4 parts of modified ferroferric oxide nanoparticles, 4 parts of acrylamide graft copolymer and 2 parts of silicate, the modified synergistic powder includes montmorillonite, kaolinite, fly ash, zeolite and lime powder, which are modified by high temperature, the modified activated carbon is modified by polyimide, hydrochloric acid solution, silane coupling agent and alcohol, the flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate, the modified ferroferric oxide nanoparticles are modified by silane coupling agent, phosphoethanolamine and sodium acrylate, and the montmorillonite, kaolinite, fly ash, zeolite and lime in the modified synergistic powder are modified by 1% mol / l 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 2 O 4 0 The powder ratio is controlled at 3:1:2:1:3, montmorillonite, kaolinite and zeolite are all ground until they pass a 100-mesh sieve. The preparation method of the modified synergistic powder is as follows: montmorillonite, kaolinite, fly ash, zeolite and lime powder are poured into a stirring device for stirring and mixing, the stirring temperature is controlled at 40°C, the stirring speed is controlled at 290r / min, deionized water is added after stirring for 5 minutes, and stirring is continued for 7 minutes to obtain a mixed material, and the mixed material is dried in a drying box to obtain a block material after drying, the block material is broken into particles passing a 10-mesh sieve, the particles are poured into a roasting device for roasting, the roasting temperature is controlled at 620°C, the roasting is carried out for 80 minutes, and the material is poured out and ground until the material passes a 200-mesh sieve to obtain To the modified synergistic powder, the preparation method of modified activated carbon: obtain activated carbon, pour the activated carbon into a hydrochloric acid solution and soak it, the mass concentration of the hydrochloric acid solution is 55%, the soaking temperature is controlled at 69°C, and after 15 minutes, it is washed with deionized water, and after drying, it is poured into polyimide, silane coupling agent and alcohol, and an ultrasonic generator is started for treatment. The power of the ultrasonic wave is controlled at 1500W, and the frequency of the ultrasonic wave is controlled at 28KHz. After 60 minutes of ultrasonic reaction, the activated carbon is washed again with deionized water, and the modified activated carbon is obtained after drying. The flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate in a ratio of 6:2:2. Potassium aluminum sulfate dodecahydrate is selected as a powder material. The preparation method of the flocculant: potassium aluminum sulfate dodecahydrate, iron salt and Aluminum sulfate is poured into deionized water, the stirring temperature is controlled at 58°C, the stirring speed is controlled at 390r / min, and after stirring for 17 minutes, it is dehydrated and dried, and poured into a grinder for grinding to obtain a flocculant. The ratio of ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate in the modified ferroferric oxide nanoparticles is controlled at 3:0.5:2.5:4. The ferroferric oxide nanoparticles are nano-scale ferroferric oxide powder. The preparation method of the modified ferroferric oxide nanoparticles is as follows: the ferroferric oxide nanoparticles, silane coupling agent, phosphoethanolamine and sodium acrylate are mixed evenly, poured into a grinding device for grinding, and poured into a plasma treatment reaction device after grinding evenly. The vacuum degree inside the plasma treatment reaction device is 4.2Pa, using radio frequency power for discharge treatment, and then washing and drying to obtain modified ferroferric oxide nanoparticles.
[0053] A method for preparing a sewage treatment agent comprises the following steps:
[0054] S1: obtain modified synergistic powder, pour it into deionized water for mixing, add calcium aluminate after mixing evenly, control the stirring temperature at 61°C, control the stirring speed at 270r / min, and stir for 24 minutes to obtain a mixed solution;
[0055] S2: Pour the modified activated carbon and calcium sulfate into the mixed solution, increase the stirring speed to 360r / min, and stir for 11 minutes to obtain a mixed solution;
[0056] S3: pouring the acrylamide graft copolymer and the silicate into the blended liquid, raising the stirring temperature to 86° C., reducing the stirring speed to 260 r / min, stirring for 55 minutes and then drying to obtain a blend;
[0057] S4: Add the flocculant and modified ferroferric oxide nanoparticles into the blend, pour into a grinding device, grind evenly, and obtain a sewage treatment agent.
[0058] Comparing conventional sewage treatment agents with the sewage treatment agents prepared in Examples 1 to 5, the sewage treatment agents prepared in Examples 1 to 5 are shown in the following table:
[0059]
[0060] Note: √ indicates that the condition exists. The more √s there are, the more obvious the condition is. 0 indicates that the condition does not exist.
[0061] It can be seen from the above table that the transparency of the sewage treatment agent prepared by the present invention is significantly improved, the concentration of suspended matter is significantly reduced, the odor is not obvious, and implementation 2 is the best embodiment.
[0062] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A sewage treatment agent, characterized in that: The sewage treatment agent comprises 40 to 50 parts of modified synergistic powder, 15 to 20 parts of calcium aluminate, 10 to 15 parts of modified activated carbon, 5 to 10 parts of flocculant, 5 to 10 parts of calcium sulfate, 1 to 5 parts of modified ferroferric oxide nanoparticles, 1 to 5 parts of acrylamide graft copolymer and 1 to 2 parts of silicate, wherein the modified synergistic powder comprises montmorillonite, kaolinite, fly ash, zeolite and lime powder, and then is modified by high temperature, the modified activated carbon is modified by polyimine, hydrochloric acid solution, silane coupling agent and alcohol, the flocculant comprises potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate, and the modified ferroferric oxide nanoparticles are modified by silane coupling agent, phosphoethanolamine and sodium acrylate; The ratio of montmorillonite, kaolinite, fly ash, zeolite and lime powder in the modified synergistic powder is controlled at 3:1:2:1:3, and the montmorillonite, kaolinite and zeolite are all ground until they pass through a 100-mesh sieve; The preparation method of the modified synergistic powder comprises the following steps: pouring montmorillonite, kaolinite, fly ash, zeolite and lime powder into a stirring device for stirring and mixing, controlling the stirring temperature at 35°C to 45°C, controlling the stirring speed at 240r / min to 320r / min, adding deionized water after stirring for 5 minutes and continuing stirring, stirring for 5 minutes to 15 minutes to obtain a mixed material, drying the mixed material in a drying box, obtaining a block material after the drying is completed, breaking the block material into particles passing through a 10-mesh sieve, pouring the particles into a roasting device for roasting, controlling the roasting temperature at 600°C to 640°C, roasting for 60 minutes to 110 minutes, pouring out the material, grinding it until the material passes through a 200-mesh sieve, and obtaining the modified synergistic powder; The preparation method of the modified activated carbon comprises the following steps: obtaining activated carbon, pouring the activated carbon into a hydrochloric acid solution for soaking, wherein the mass concentration of the hydrochloric acid solution is 45% to 65%, the soaking temperature is controlled at 65° C. to 75° C., washing with deionized water after 15 minutes, pouring into polyimide, silane coupling agent and alcohol after drying, starting an ultrasonic generator for treatment, controlling the power of the ultrasonic wave at 1200W to 1500W, and the frequency of the ultrasonic wave at 22KHz to 28KHz, and after ultrasonic reaction for 60 minutes to 100 minutes, washing the activated carbon again with deionized water, and obtaining the modified activated carbon after drying; The flocculant includes potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate in a ratio of 6:2:2, and the potassium aluminum sulfate dodecahydrate is selected in powder form; The preparation method of the flocculant is as follows: potassium aluminum sulfate dodecahydrate, iron salt and aluminum sulfate are poured into deionized water, the stirring temperature is controlled at 55°C to 65°C, the stirring speed is controlled at 320r / min to 400r / min, the mixture is stirred for 15 to 30 minutes, and then dehydrated and dried, and poured into a grinder for grinding to obtain a flocculant; The preparation method of the modified ferroferric oxide nanoparticles comprises the following steps: uniformly mixing ferroferric oxide nanoparticles, a silane coupling agent, phosphoethanolamine and sodium acrylate, pouring the mixture into a grinding device for grinding, and then pouring the mixture into a plasma treatment reaction device after uniform grinding, wherein the vacuum degree inside the plasma treatment reaction device is 4Pa to 4.2Pa, performing discharge treatment using a radio frequency power supply, and then cleaning and drying to obtain the modified ferroferric oxide nanoparticles.
2. A sewage treatment agent according to claim 1, characterized in that: The ratio of the ferroferric oxide nanoparticles, the silane coupling agent, phosphoethanolamine and sodium acrylate in the modified ferroferric oxide nanoparticles is controlled at 3:0.5:2.5:4, and the ferroferric oxide nanoparticles are nano-scale ferroferric oxide powders.
3. A sewage treatment agent according to claim 1, characterized in that: The sewage treatment agent is preferably 47 parts of modified synergistic powder, 18 parts of calcium aluminate, 13 parts of modified activated carbon, 7 parts of flocculant, 6 parts of calcium sulfate, 4 parts of modified ferrosoferric oxide nanoparticles, 3 parts of acrylamide graft copolymer and 2 parts of silicate.
4. A method for preparing a sewage treatment agent as claimed in claim 1, characterized in that: The following steps are involved: S1: obtain modified synergistic powder, pour it into deionized water for mixing, add calcium aluminate after mixing evenly, control the stirring temperature at 45°C to 65°C, control the stirring speed at 240r / min to 320r / min, and stir for 15 minutes to 30 minutes to obtain a mixed solution; S2: Pour the modified activated carbon and calcium sulfate into the mixed solution, increase the stirring speed to 320r / min-400r / min, and stir for 5-15 minutes to obtain a mixed solution; S3: pouring the acrylamide graft copolymer and the silicate into the blended liquid, raising the stirring temperature to 65° C. to 95° C., reducing the stirring speed to 240 r / min to 320 r / min, stirring for 45 to 60 minutes and then drying to obtain a blend; S4: Add the flocculant and modified ferroferric oxide nanoparticles into the blend, pour into a grinding device, grind evenly, and obtain a sewage treatment agent.
Citation Information
Patent Citations
A heavy metal wastewater treatment agent
CN111018016B
Crotonic acid and acrylic acid copolymer modified ferroferric oxide nano granules with silicon structure as well as preparation and application thereof
CN102527351A
Method for utilizing modified mordenite to treat urban recycled water
CN104710079A
Activated carbon modifying method
CN107175076A
Magnetic ferroferric oxide nanoparticles, and plasma modification method and application thereof
CN107511132A